Prediction of anaerobic capacity from lactate kinetics during constant supramaximal test - روح الله نیکویی; مجید نظری; حمید معرفرتی (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: The aim of present study was to investigate the prediction of anaerobic capacity from lactate kinetic during supramaximal exercise. Methods: Fifteen active males with average values of age 22 ± 3.64 and weight 74 5.74 performed an incremental test for Pax determination, a constant supramaximal test with %110 of their Pmax and Wingate anaerobic test as the reference test in three separated sessions. Blood lactate concentration was measured before starting test, every minute during the test, immediately after exercise, and during recovery period at intervals 3, 6, and 9 min. Lactate changes (A La), time constant of lactate changes (A TLa), maximum lactate accumulation (Lamax) were calculated from lactate-time graph by Microcal Origin software. The relationship between variables was measured by Pearson correlation test and multiple regression analysis was used for ability of prediction. Results: Significant correlation was found between Lamax (P<0.05), ALa (P<0.01), ATLa (P<0.01) during the supramaximal test and ATLa (P<0.01), Lamax (P<0.01) during recovery period with anaerobic capacity. Anaerobic capacity was predictable from lactate kinetic parameters during supramaximal test (r^{2}=0.71 P<0.01) the prediction was not possible from these parameters during test and recovery period from it (r^{2}=0.40, P<0.01) . Conclusion: In summary, our results showed that lactate kinetic parameters during supramaximal test can be used for prediction of anaerobic capacity.